The Routledge handbook of community-based tourism management concepts, issues & implications - Walia, Sandeep Kumar
"This Handbook offers an up-to-date and comprehensive overview of core themes and concepts in community-based tourism management. Providing interdisciplinary insights from leading international scholars, this is the first book to critically examine the current status of community-based tourism.